ANALISIS PENGARUH STRUKTTUR CORPORATE GOVERNANCE TERHADAP PERUSAHAAN YANG MENGALAMI FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Publik yang tercatat di BEI pada tahun 2005 — 2009) - Dame Siagian (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This study to investigate the influence of corporate governance structure on financial distress. The samples are manufactired firms which has been listed in Indonesia Stock exchange from 2005-2009. The research method is linier regression. The results show that the number of board of management, institutional ownership, family ownership and the number of audit committee have been influence on financial distress.Keywords : Corporate Governance Structure, and Financial Distress